2017
DOI: 10.3389/fmicb.2017.02555
|View full text |Cite
|
Sign up to set email alerts
|

The Mitochondrial GTPase Gem1 Contributes to the Cell Wall Stress Response and Invasive Growth of Candida albicans

Abstract: The interactions of mitochondria with the endoplasmic reticulum (ER) are crucial for maintaining proper mitochondrial morphology, function and dynamics. This enables cells to utilize their mitochondria optimally for energy production and anabolism, and it further provides for metabolic control over developmental decisions. In fungi, a key mechanism by which ER and mitochondria interact is via a membrane tether, the protein complex ERMES (ER-Mitochondria Encounter Structure). In the model yeast Saccharomyces ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
3

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 73 publications
0
15
0
3
Order By: Relevance
“…In particular, Mig1, Leu1, and Lys4 all influence cell wall-related phenotypes, and an observed capsule defect was attributed to cell wall changes in a leu1 mutant (42,58,59). The connection between mitochondrial function and cell wall integrity is well established in C. albicans (60)(61)(62)(63)(64)(65). For example, a screen of mutants hypersensitive to cell wall stress identified a role for the Ccr4 deadenylase in targeting transcripts for mitochondrial functions (62).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, Mig1, Leu1, and Lys4 all influence cell wall-related phenotypes, and an observed capsule defect was attributed to cell wall changes in a leu1 mutant (42,58,59). The connection between mitochondrial function and cell wall integrity is well established in C. albicans (60)(61)(62)(63)(64)(65). For example, a screen of mutants hypersensitive to cell wall stress identified a role for the Ccr4 deadenylase in targeting transcripts for mitochondrial functions (62).…”
Section: Discussionmentioning
confidence: 99%
“…This observation led to the subsequent identification of connections for specific mitochondrial proteins including Sam37 and Gem1 (52,54). Sam37 is important for maintaining mitochondrial DNA (mtDNA), cell wall integrity, caspofungin tolerance, and ultimately virulence (61), while the mitochondrial GTPase, Gem1, plays a role in maintaining mitochondrial morphology and contributing to cell wall integrity in a Cek1-dependent manner (63). Recently, a role has been described for mitochondria in influencing the cell wall and contributing to a process called "masking" that results in avoidance of recognition by immune cells; the influence was attributed to modes of respiration or to hypoxia and connected to signaling via the cyclic AMP (cAMP)-protein kinase A (PKA) pathway (60,64).…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between Miro proteins and MERCs started to be investigated when, in 2011, two research groups identified Gem1p, the yeast ortholog of mammalian Miro1, as a crucial regulator of the ER-mitochondrial encounter structure (ERMES), a protein complex that tethers mitochondria and ER in yeast ( 15 , 80 ). Association of Gem1p to ERMES controls phospholipid exchange for lipid biosynthesis between mitochondria and ER ( 15 ) and regulates mitochondrial division and morphology ( 81 83 ). The localization of dMiro at MERCs was also demonstrated in Drosophila neural stem cells and dopaminergic neurons ( 17 , 84 ), as well as mammalian Miro1 in COS-7 cells, HeLa cells, MEFs, human fibroblasts, and human iPSC-derived neurons ( 14 , 15 , 67 , 84 , 85 ).…”
Section: Miro1 As a Regulator Of Mitochondrial-er Contact Sitesmentioning
confidence: 99%
“…a The worm C. elegans ( glp-4; sek-1 ) was infected with C. albicans strains as follows: wild type, a DNM1 deletion strain ∆∆dnm1 or a complemented mutant strain (+ DNM1 ). The strains are described in (Koch et al 2018), and the worm C. albicans infection method is described in detail in our previous publication (Koch et al 2017). Shown are representative images after 48 h of infection.…”
Section: Mitochondrial Fission In Pathogenic Fungal Speciesmentioning
confidence: 99%